Orthodontics-Awareness Amongst Medical Students - SEZEN ERHAMZA, Türkan; ARSLAN ÇARPAR, Kübra A (Orthodontic Journal of Nepal, 2020)
Introduction: The study aimed to evaluate the knowledge and awareness of orthodontics, a specialty of dentistry,amongst Medical Students. Materials and Method: A sample of 550 students (279 female, 226 male aged between 18 and 36 years) were attented.Of the subjects, 58.6% (n = 296) were preclinical students, while 41.4% (n = 209) were clinical students. The students were informed about the questionnaire and asked to fill in the questionnaire forms. For the comparison of data between groups (gender, level of education), the chi-square test was used. A chi-square test was used for statistical evaluation and the p-value < 0.05 was considered statistically significant. Result: 385 students (76.2%) had heard the term orthodontics although 41.2% of the subjects knew that orthodonticswas concerned with malocclusions and their treatment. The question about treatment procedures was answeredas scaling by 35.8%, tooth polishing by 40%, tooth aligning by 89.9% of the students. The percentage of knowingorthodontics to be related to tooth aligning showed a significant difference between female and male (p = 0.006), andpreclinical and clinical students (p = 0.033). Of the participants, 42.8% thought that dentures, 83% brackets, 78.8% ofremovable appliances were used by orthodontists. Conclusion: Our results have shown that medical students should have more information about orthodontics, aspecialty of dentistry.